Tinjauan Literatur: Faktor-Faktor Penyebab Kelengkapan Pengisian Rekam Medis Rawat Inap Rumah Sakit - Putu Adiz Siwayana; Ika Setya Purwanti; Putu Ayu Sri Murcittowati (Poltekkes Kemenkes Semarang, 2020)
Every health facility, whether it is primary, secondary, tertiary, is required to maintain medical records in order to achieve administrative order. Incomplete (incomplete) medical records will affect the service process provided by health workers and have an impact on the quality of service of a hospital. This study aims to determine the factors causing the incomplete filling of inpatient medical records. This study uses a literature review method. The strategy in searching literature reviews is using Google Scholar. In the search phase, articles are limited to publications from 2015-2020. The keywords used are the factors causing incomplete medical record filling. The search results obtained 10 articles and then 5 articles were taken. The results of the literature review show that the factors causing the incompleteness of filling in medical records as a whole can be seen from the lack of knowledge, motivation and awareness of medical personnel about medical records. The meeting as a means of communication between caregivers and management has not yet been implemented to discuss evaluation and monitoring as well as sanctions for officers who do not complete medical records. lack of socialization on filling out medical records. Unsystematic arrangement of medical record forms. Limited availability of funds or budget to support medical record service activities. Conclusion Hospitals need to pay attention to the factors causing the incompleteness of filling in medical records so that filling in medical records is complete according to standards. So that the quality of service, especially the quality of patient medical records.AbstrakSetiap fasilitas kesehatan baik tingkat primer, sekunder, tersier wajib menyelenggarakan rekam medis agar tercapainya tertib administrasi. Ketidaklengkapan (Incomplete) rekam medis akan berpengaruh terhadap proses pelayanan yang diberikan oleh petugas kesehatan dan berdampak pada kualitas pelayanan suatu rumah sakit. Penelitian ini bertujuan untuk mengetahui faktor penyebab ketidaklengkapan pengisian rekam medis rawat inap. Penelitian ini menggunakan metode literatur review. Strategi dalam pencarian literatur review menggunakan Google Scholar. Pada tahap pencarian artikel dibatasi terbitan dari tahun 2015-2020. Kata kunci yang digunakan adalah Faktor Penyebab ketidaklengkapan pengisian rekam medis. Hasil penelusuran artikel didapatkan 10 artikel dan selanjutnya diambil 5 artikel. Hasil dari literatur review didapatkan faktor penyebab ketidaklengkapan pengisian rekam medis secara keseluruhan, penyebabnya dapat dilihat dari kurangnya pengetahuan, motivasi dan kesadaran dari petugas rekam medis tentang rekam medis. Belum terlaksananya rapat sebagai wadah komunikasi antara pemberi asuhan dan manajemen yang membahas evaluasi dan monitoring serta sanksi bagi petugas yang tidak mengisi rekam medis dengan lengkap. kurangnya sosialisasi pengisian rekam medis. Susunan formulir rekam medis yang tidak sistematis. Terbatasnya ketersediaan dana atau anggaran untuk mendukung kegiatan pelayanan rekam medis. Kesimpulan Rumah sakit perlu memperhatikan faktor penyebab ketidaklengkapan pengisian rekam medis sehingga pengisian rekam medis menjadi lengkap sesuai dengan standar. Sehingga mutu dari pelayanan terutama mutu rekam medis pasien.